Intensity Of Soil Treatment And Frequency Of Inorganic Fertilizer Application On Nutrient Levels And Growth Of Palm Oil (Elaeis guineensis Jacq) At The Replanting Stage - Hendra Pangondian Sihaan; Wawan Wawan; M. Amrul Khoiri (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Oil palm is a plantation crop that produces vegetable oil, and people highly need it, so it requires efforts to increase its production. One way is by utilizing existing land without having to open new oil palm plantation areas with replanting. This study aimed to analyze the effect of fertilization frequency on different tillage and to get the best fertilization frequency on different tillage on leaf nutrient levels and growth of oil palm plants. This research experimented with a split-plot design (SPD) with a randomized block basic design. The factors tested in this study consisted of the main plot, e.g., tillage (No tillage, 1 time of tillage, 2 times of tillage) and subplots, e.g., the fertilization frequency (D1: 5 times frequency of NPK fertilization D2: 4 times frequency of NPK fertilization D3 : 3 times frequency of NPK fertilization). The two factors were combined, and 12 treatment combinations were obtained. Each treatment combination consisted of 3 groups, totaling 36 experimental units. Each experimental unit consisted of 2 plants, so 72 plants were obtained. The data obtained were analyzed using variance and further tested with the honest significant difference test (BNJ) at the 5% level and advanced test analysis using the Satker application (SAS). This study showed that NPK fertilization with a frequency of 2 times in 2 times tillage increased vegetative plant growth (increased stem circumference). The main plot of tillage two times increased leaf nutrient content (leaf N content) and plant vegetative (plant height gain and stem circumference increase). NPK fertilization with a frequency of 2 times increased plant growth (increased stem circumference).